TINJAUAN HUKUM TERHADAP KLAIM PENYESUAIAN NILAI KONTRAK DALAM PENYELESAIAN KONTRAK TAHUN JAMAK KONSTRUKSI TRANSMISI - , Vony Sulistiyorini, S.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In the implementation of transmission construction projects often have problems that gave rise to the injured party. Losses can be money, time and quality,as result of work or product. This trend continued in the construction of transmission in Indonesia. This thesis entitled "Legal review of claims adjustment to contract value in the completion of multi years contract on transmission constructionâ. The issues raised in this thesis focuses on how to solve problems of claim that arise on construction development projects owned by the Government due to a delay in execution of works from year 2003 to 2010. The method used in this thesis is to approach the problem using normative juridical and empirical juridical methods, and conclusions reached by induction. The primary data is used in this research is taken from contract 500 kV Transmission Line project â Lot B, whereas the secondary data obtained from literature. The appearance of the claim due to the contractual conditions are not clear in the end lead to dispute. Disputes can open opportunities for the parties to justify their own purpose of doing harm to the parties, the State or private, owner and suppliers. In order to avoid conflicts that required a clear and detailed document that stated in the contract documents. This study shows that the escalation article or adjustment contract price is required as a principle of fairness in multi-year contract, taking unpredictable field conditions while the price of materials is very unstable and vulnerable to international economic and political conditions. The resolution of these issues is not through the courts (outside the law) that is by way of consensus, but still guided by the agreements that have been agreed.